KOTAK AJAIB BERBASIS COGNITIVE NEUROSAINS UNTUK PENINGKATAN PERILAKU HIDUP SEHAT DI SEKOLAH - Elizar Elizar; Agung Prihatmojo; Badawi Badawi; Mutia Lutfi (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2023)
The implementation of face-to-face learning requires strict discipline of healthy behavior. Children are expected to be able to adapt to the new habits they have to face. Disciplining children's healthy behavior during the implementation of limited learning is very important, so that children are protected from the risk of virus transmission. The purpose of community service is to provide an alternative to disciplining children in face-to-face learning through the use of Cognitive Neuroscience-Based Magic Box learning media. The service was held at Aisyiyah Bustanul Athfal (ABA) V Kotabumi Kindergarten on October 19 2022. In this activity those involved were lecturers, teachers and students of Muhammadiyah Kotabumi University as well as teachers and students of ABA V Kindergarten as partners. The Magic Box Based on Cognitive Neuroscience is a mystery box as a learning medium for disciplining children's healthy behavior with a game method made for the introduction of concrete objects according to the stages of children's cognitive development. These objects are around children and can be used, such as masks, hand sanitizers, tissues, and so on. The methods in this service activity are socialization, training, mentoring, monitoring and evaluation. The results of this activity are 1. Increasing teacher knowledge and skills in learning neuroscience, 2. Teachers have learning media to increase the introduction of health protocol tools in applying healthy behavior discipline in learning.